(untitled) (Journal of Tourism and Himalayan Adventures, 2019)
This paper discusses some of the trekking processes in Nepal. It has focused on the cross-cultural behavior of the guests, the hosts and the agents in various situations during the trekking in Nepal. The hosts, guests and the agents are culturally different and thus heterogeneity is ever present in their encounters. But their encounter in the trekking is not simply determined by their cultural differences; there is a heavy influence of power. The cross-cultural behavior of the guests, the hosts, and the agents are dependent upon the exercise of power and authority during the period of trekking in Nepal.